Synthesis of Molecularly Imprinted Polymer for Sterol Separation - Ratanaporn Yuangsawad; Nuengruthai Chuayrueng; Nattawat Nonthanasin; Krittin Binabdullah; Duangkamol Na-Ranong (My University, 2016)
Molecular imprinted polymer (MIP) was prepared by bulk polymerization in acetone using acrylamide as a functional monomer, ethylene glycol dimethacrylate as a crosslinker, stigmasterol as a template and benzoyl peroxide as an initiator. The obtained MIPs were characterized using a scanning electron microscope and a fourier transform infrared spectrophotometer. Performance in sterol adsorption of MIPs prepared under various conditions was investigated using a model solution of phytosterols in heptane, comparing with a nonimprinted polymer (NIP). Statistical analysis revealed that the amounts of crosslinker and template strongly affected the performance of MIP while the amount of solvent slightly affected the performance of MIP. MIP synthesized under the optimal condition had adsorption capacity of 1.28 mgsterols/gads which were 1.13 times of NIP.
Keywords: Ethylene glycol dimethacrylate; Molecularly imprinted polymer; Precipitation polymerization; Bulk polymerization; NIP; Analytical chemistry methods development